3b+7-1=-3
3b+6= -3
Move +6 to the other side. Sign changes from +6 to -6.
3b+6-6= -3-6
3b=-9
Divide by 3
3b/3=-9/3
b= -3
3x+1-6x=7
3x-6x+1= 7
-3x+1= 7
Move +1 to the other side. Sign changes from +1 to -1.
-3x+1-1= 7-1
-3x=6
Divide by -3
-3x/3= 6/-3
x= -2
312=-6(7x-3)
Mutiply the bracket by -6
312= (-6)(7x)(-6)(-3)
312= -42x+18
Move +18 to the other side.
312-18= -42x+18-18
312-18= -42x
294=- 42x
divide by -42
294/-42= -42/-42x
x= -7
-4(4n-8)=128
Mutiply the bracket by -4
(-4)(4n)(-4)(-8)= 128
-16n+32= 128
move +32 to the other side
-16n+32-32= 128-32
-16n= 96
divide by -16
-16/-16n= 96/-16
n= -6
Answers:
b= -3
x= -2
x= -7
n= -6